THE IMPACT OF THE BOYCOTT ON KFC'S DECLINING PURCHASING POWER - Mica Siar Meiriza; Adha Mahyundari; Aulia Rahmadhani; Nabila Umaira; Muhammad Reyhan Satria (TECHNOBIZ : International Journal of Business, 2025)
This ponder analyzes the affect of the boycott on KFC's acquiring control and money related execution due to its affiliation with back for Israel. The boycott, driven by the worldwide Boycott, Divestment and Sanctions (BDS) development, picked up far reaching bolster, counting in Indonesia, where open calls through social media and a fatwa from the Indonesian Ulema Committee intensified its affect. This investigate utilized a subjective approach through interviews with KFC representatives to pick up viewpoints on the affect of the decay in deals and the ensuing impacts on resolve and work security. The comes about appeared that the boycott activated a 20-30% drop in KFC's footfall and income, and contrarily affected the brand picture and work steadiness of workers. To overcome these impacts, KFC Indonesia looked for to progress item quality, propelled extraordinary advancements, and committed to being more straightforward in tending to social issues to preserve shopper bolster.